Application Systems Available In UNIMED Language Skills Text - Rabiah Adawi (Budapest International Research and Critics in Linguistics and Education (BirLE) Journal, 2020)
This study aims to describe the attitude appraisal system contained in the French thesis text at UNIMED. The method used in this study is a descriptive qualitative method. The research sample is the French thesis text at UNIMED on behalf of Ayokta Ghea M. Panjaitan, NIM. 21013001 where the type of thesis is linguistics with the title Analyze De Champ Lexical Des Activités Des Yeux En Français (Analysis of the Lexical Meaning of Eye Activity in French) totaling 58 pages with the highest GPA of 3.85 and Irna Fadillah Nasution, NIM. 2101131002 with a GPA of 3.45 with the title of the thesis Analyze Sémiotique De La Publicite Femme De Beauté Dans Le Magazine Femme Actuelle (Semiotic Analysis of Beauty Advertisements in the French Magazine Femme Actuelle) totaling 60 pages that have been validated by native speakers teaching at the French Language Education Study Program UNIMED in 2015 and also teaches at the Alliance Française (AF) called Marine Petite. Data were analyzed using the Simple Concordance Program (SCP) concordance program software using the Apraisal system, namely: Attitude Apraisal. The results showed that the Apraisal System in the French Thesis text at UNIMED was the Paradigmatic System because the Apraisal System in the French thesis text consisted of (a). Gender (le gendre), which consists of: masculine (masculin) and feminine (féminin) and (b). Total (le nombre), which consists of: single (singulier) and plural (pluriel).